ANALYSIS OF CORROSION RATE AND HARDNESS VALUE OF LOW CARBON STEEL COATED WITH PAni-TiO2 SYNTHESIZED BY ELECTRODEPOSITION - Sulistyaningsih, Eka; Lestari, Nidia; Yusuf, Muhammad; Wahyuningtyas, Dewi (Indonesian Physical Review, 2023)
In the industrial world, carbon steel has been widely used. Corrosion of carbon steel cannot be avoided, so many studies have been carried out to overcome Corrosion. One of the efforts to overcome Corrosion is by coating. Low-carbon steel coating was done by combining TiO2 and polyaniline (PAni), which was carried out by electrodeposition. A carbon steel specimen that has been coated is corroded by immersing it in an acid and salt medium. After Corrosion, the specimen is tested for hardness. The specimen without inhibitor has a hardness value of 131 kg/mm2, while the specimen with the highest hardness value is a specimen coated with PAni 10-1 M and TiO2 10-4 M at 336 kg/mm2. Based on visual observation, the Corrosion that occurs is uniform.